2021
DOI: 10.1097/md.0000000000025994
|View full text |Cite
|
Sign up to set email alerts
|

Dual-scale categorization based deep learning to evaluate programmed cell death ligand 1 expression in non-small cell lung cancer

Abstract: In precision oncology, immune check point blockade therapy has quickly emerged as novel strategy by its efficacy, where programmed death ligand 1 (PD-L1) expression is used as a clinically validated predictive biomarker of response for the therapy. Automating pathological image analysis and accelerating pathology evaluation is becoming an unmet need. Artificial Intelligence and deep learning tools in digital pathology have been studied in order to evaluate PD-L1 expression in PD-L1 immunohistochemistry image. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0
2

Year Published

2022
2022
2025
2025

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 38 publications
(80 reference statements)
0
4
0
2
Order By: Relevance
“…The assessment results of trained pathologists' evaluation of PD-L1 expression are usually more accurate than those of untrained pathologists (33). It takes extensive professional learning and training for an untrained pathologist to become experienced (34). Previous studies have indicated that the assessment of PD-L1 expression by untrained pathologists has lower intraclass consistency compared with that by highly trained pathologists (35).…”
Section: Discussionmentioning
confidence: 99%
“…The assessment results of trained pathologists' evaluation of PD-L1 expression are usually more accurate than those of untrained pathologists (33). It takes extensive professional learning and training for an untrained pathologist to become experienced (34). Previous studies have indicated that the assessment of PD-L1 expression by untrained pathologists has lower intraclass consistency compared with that by highly trained pathologists (35).…”
Section: Discussionmentioning
confidence: 99%
“…The inclusion of patients in immunochemotherapy protocols with Pembrolizumab monotherapy or its combinations passes through PDL1 positive cell count, since inter-observer variability can easily shift the therapeutic plan due to the low amount of positive cells needed to reach the TPS cut-off [9]. Indeed, attempts to use DNN for TPS computation in lung cancer already exist in literature [50]. Moreover, given the growing knowledge about disease molecular therapy targets and interest in Precision Medicine, a future increase in the number of routinely analyzed immunohistochemical predictive and prognostic markers becomes a reasonable educated guess [15].…”
Section: Discussionmentioning
confidence: 99%
“…The model's classification accuracy was 74.51%, higher than trainees (71.55%) but lower than subspecialist and non-subspecialist pathologists (97.06% and 84.03%, respectively). In another study, TPS assessment reached high performance in terms of sensitivity and specificity in both 1% and 50% cut-off points [112]. The classification was performed on slides stained with 22C3 antibody, and the proposed patch-based dual-scale categorization method based on VGG16 architecture achieved higher performance compared to VGG16.…”
Section: Pd-l1 Expression Statusmentioning
confidence: 95%